Evaluating Audio Description and BPS Visitor Experience in Titanic Belfast - Wang, Xi; Crookes, Danny; Harding, Sue-Ann; Johnston, David (Journal of Audiovisual Translation, 2020)
This paper presents the results of a study that evaluates audio description (AD) and visitor experience with a group of blind and partially sighted (BPS) visitors to a real-world visitor attraction—Titanic Belfast. We apply the 10-facet model of visitor experience of Packer and Ballantyne (2016) for the first time in the context of accessibility, and through this we highlight accessibility issues which arose during the study. We identify two categories in our qualitative analysis that the model (Packer & Ballantyne, 2016) cannot cover. We also model the factors that influence visitor experience and apply them to the later approach of Packer, Ballantyne, & Bond’s (2018) Dimensions of Visitor Experience (DoVE) Adjective Checklist. The checklist is based on their previous 10-facet model, and translated and refined into 15 dimensions. Although the DoVE checklist is not specifically designed for the context of accessibility, we found that it is sufficiently comprehensive to model accessibility aspects of the museum AD and visitor experience for BPS visitors.